PARC (Relational Art Performance as Healing - RAPH): performance and somatic experiencing - Alice (Universidade Federal do Estado do Rio de Janeiro, Rio de Janeiro, Brazil), Tania (Revista Brasileira de Estudos da Presença, 2022)
The article proposes an enlargement of Pablo Helguera’s concept of socially engaged art, used to describe artistic works that blur the boundaries between social project and artistic project. From the analysis of the creation process of the performance “Bate-Papo na Cama” (Bed Time Talking), which consists in putting my bed in public spaces of different countries in the world, the article aims at thinking how the artistic practice can be intensified and deepened by the resources offered by Somatic Experiencing (SE). The practice, developed by Peter Levine, helps to think, design, and implement artistic border projects, not only between artistic and social projects, but that blurs frontiers with therapeutic plans, whether individual or collective, generating the concept of Relational Art Performance as Healing – RAPH.